Strengths, challenges, and gaps in linkage to primary care among hospitalized individuals who are homeless in Vancouver, British Columbia. Issue 2 (2nd July 2020) - Yu, Alec Chu Ming; Gadermann, Anne; Palepu, Anita
ABSTRACT: Individuals who are homeless in the Canadian city of Vancouver, British Columbia have an increasing burden of chronic medical conditions, resulting in rising use of hospital services. Although continued efforts have been made to improve accessibility, barriers to primary care linkage and utilization still exist. Our study explored the strengths, barriers, and gaps in how inpatients who are homeless are connected to primary care through semi-structured qualitative interviews with patients ( n = 22) and healthcare providers ( n = 7) with experience in caring for patients who are homeless. Patients identified cell phone ownership and use of commitment devices as strengths, while clinics with long wait times, or those proximal to areas of prevalent drug use, were seen as barriers. Providers perceived that low priority was given to primary care linkage within hospitals, and that early and bidirectional communication with hospital staff is vital, particularly around discharge planning. Patients and providers then identified major gaps in service, which included a need for peer health navigation, technology-assisted outreach, and improved service distribution.